Intenzionalità, causazione mentale e colpevolezza - De Caro, Mario (Filosofia Morale/Moral Philosophy, 2022)
In order for a subject to be correctly said to be guilty of a wrongful act, their conscious mental states have to have been the cause of that act: ie, a mens rea has to have been the cause of a corresponding actus reus. This definition, although quite satisfactory from the practical point of view, leaves open at least two questions that concern the philosophy of action that will be addressed in this article. The first question – originated by the discussions on Davidson’s theory of action – is that guilty is defined by the existence of a causal link between a mens rea and an actus reus is not correct, because there are causal links (the so-called “deviant causal chains”) that appear not to generate guilt. The second question derives from recent scientific data that seem to prove that in many cases consciousness does not play a role in the production of our actions (and, indeed, according to some scholars, simply plays no role ever). If this is so, many, and perhaps all, of our attributions of guilt are in fact unjustified.